Proportionality and Karlsruhe's ultra vires verdict: Ways out of constitutional pluralism? - Martin Höpner (Max Planck Institute for the Study of Societies, 2021)
In May 2020, for the first time in its history, the Federal Constitutional Court (FCC) of Germany declared Union acts as being ultra vires. According to the FCC, the European Central Bank (ECB) and the Court of Justice of the European Union (CJEU) had acted beyond their mandates because they did not apply strong proportionality standards to the ECB's Public Sector Purchase Programme (PSPP). The resulting stalemate within constitutional pluralism has revived the discussion about the possible introduction of an Appeal Court with the 'final say' over constitutional conflict. As the analysis of the PSPP conflict shows, such a judicial authority would reach its limits the more we move from the surface to the core of the struggles between European and national constitutional law. The different readings of proportionality are difficult to bridge, and the mutually exclusive claims about the nature of the supremacy of European law are not accessible to compromise at all. We should therefore not expect too much from an Appeal Court, if it were introduced. – – Im Mai 2020 hat das deutsche Bundesverfassungsgericht (BVerfG) erstmals europäische Rechtsakte als ultra vires klassifiziert. Dem Urteil zufolge haben die Europäische Zentralbank (EZB) und der Europäische Gerichtshof (EuGH) ihr Mandat überspannt, indem sie auf eine strenge Verhältnismäßigkeitsprüfung des Public Sector Purchase Programme (PSPP) der EZB verzichteten. Das Patt zwischen den Gerichten hat die Debatte über ein europäisches Berufungsgericht, das in europäischen Verfassungsgerichten das letzte Wort sprechen könnte, neu belebt. Wie die Analyse des PSPP-Konflikts verdeutlicht, würde ein neues Höchstgericht an Grenzen stoßen, sobald die Tiefenstruktur des Spannungsfelds zwischen Europarecht und mitgliedstaatlichem Verfassungsrecht in den Blick gerät. Die unterschiedlichen Lesarten des Verhältnismäßigkeitsprinzips lassen sich nur schwer überbrücken und der Konflikt über die Natur des Vorrangs des Europarechts ist Kompromissen gänzlich unzugänglich. Von einem Berufungsgericht, würde es gegründet, sollte daher nicht zu viel erwartet werden.
hdl:21.11116/0000-0007-EACA-E
Keywords: 300; constitutional conflict; Court of Justice of the European Union; European Central Bank; European law; European Monetary Union; Federal Constitutional Court; proportionality; Bundesverfassungsgericht; Europäische Währungsunion; Europäische Zentralbank; Europäischer Gerichtshof; Europarecht; Verfassungskonflikt; Verhältnismäßigkeit